Understanding the implications of Social Translucence for systems supporting communication at work - Szostek, Agnieszka Matysiak; Karapanos, Evangelos; Eggen, Berry; Holenderski, Mike (My University, 2008)
In this paper we describe a study that explored the implications of the Social Translucence framework for designing systems that support communications at work. Two systems designed for communicating availability status were empirically evaluated to understand what constitutes a successful way to achieve Visibility of people's communicative state. Some aspects of the Social Translucence constructs: Visibility, Awareness and Accountability were further operationalized into a questionnaire and tested relationships between these constructs through path modeling techniques. We found that to improve Visibility systems should support people in presenting their status in a contextualized yet abstract manner. Visibility was also found to have an impact on Awareness and Accountability but no significant relationship was seen between Awareness and Accountability. We argue that to design socially translucent systems it is insufficient to visualize people's availability status. It is also necessary to introduce mechanisms stimulating mutual Awareness that allow for maintaining shared, reciprocical knowledge about communicators' availability state, which then can encourage them to act in a socially responsible way.
Keywords: Accountability; Ambiguity; Awareness; Mediated communication; Social Translucence; Socially responsible behaviour; Visibility